The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1071/cp20498
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation technologies for iron and zinc biofortification and bioavailability in cereal grains

Abstract: Iron (Fe) and zinc (Zn) are recognised as micronutrients of clinical significance to public health globally. Major staple crops (wheat, rice and maize) contain insufficient levels of these micronutrients. Baseline concentrations in wheat and maize grains are 30 µg/g for Fe and 25 µg/g for Zn, and in rice grains, 2 µg/g for Fe and 16 µg/g for Zn. However, wheat grains should contain 59 μg Fe/g and 38 μg Zn/g if they are to meet 30–40% of the average requirement of an adult diet. Scientists are addressing malnut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 153 publications
0
2
0
Order By: Relevance
“…Domesticated cereals often have better and more distinguishing qualities than their wild counterparts. For example, compared to cultivated soybean seeds, natural soybean seeds have higher oil content and less protein (Ibrahim et al, 2021). Domestication has been a dynamic process throughout history.…”
Section: Re-domestication Of Current Cultivated Cropsmentioning
confidence: 99%
“…Domesticated cereals often have better and more distinguishing qualities than their wild counterparts. For example, compared to cultivated soybean seeds, natural soybean seeds have higher oil content and less protein (Ibrahim et al, 2021). Domestication has been a dynamic process throughout history.…”
Section: Re-domestication Of Current Cultivated Cropsmentioning
confidence: 99%
“…Regarding selection of lowantinutrient genotypes, Ragi et al (2022) identified several promising maize hybrids produced from inbred lines of wildtype and subtropically adapted low-phytate mutants (lpa1-1). In addition to the above genetic approaches, Ibrahim et al (2022) argued that precise genome editing tools (such as CRISPR/Cas9) can deliver new micronutrient biofortified cultivars with no linkage-drag and biosafety issues.…”
Section: Genetic Biofortificationmentioning
confidence: 99%
“…Dicoccoides ) ( 13 ), which can be efficiently utilized by wheat breeders to transfer in the background of high yielding and disease resistant hexaploid wheat genotypes. A breeding target of > 59 μg g –1 Fe, and 38 μg g –1 Zn in wheat grains ( 14 ) against the baseline level of 30 μg g –1 Fe, and 25 μg g –1 Zn would be sufficient to meet the 30–40% of the average daily requirement of an adult. However, bioavailability of Fe and Zn in wheat is greatly limited due to the presence of phytic acid (PA, 0.4–2.0%), an anti-nutrient ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%